Automated Driving and Driver Assistance Systems. - Denton, Tom ([Place of publication not identified] : Routledge, 2019)
Automated vehicles are set to transform the world. Automated driving vehicles are here already and undergoing serious testing in several countries around the world. This book explains the technologies in language that is easy to understand andaccessible to all readers. It covers the subject from several angles but in particular shows the links to existing ADAS technologies already in use in all modern vehicles. There is a lot of hype in the media at the moment about autonomous or driverless cars, and while some manufacturers expect to have vehicles available from 2020, they will notsoon take over and it will be some time before they are commonplace. However, it is very important to be ready for the huge change of direction that automated driving will take. This is the first book of its type available and complements Tom Denton's other books.
1. Introduction 2. Safety 3. Advanced driver assistance systems (ADAS) 4. Automated driving technologies 5. Social and human issues 6. Case studies 7. Website References
OCLC-licensed vendor bibliographic record.
Keywords: TRANSPORTATION / Automotive / Repair & Maintenance; TECHNOLOGY / Engineering / Mechanical; Automated vehicles; Driver assistance systems; Motor vehicles -- Technological innovations